Chinese Enough : Homestyle Recipes for Noodles, Dumplings, Stir-Fries, and More - Cho, Kristina (New York, NY : Artisan, 2024)
"Bringing together her Cantonese heritage, Midwestern upbringing, and sunny California feel for ingredients, Kristina Cho shares an irresistible approach to cooking that is Chinese Enough... This personal collection of recipes celebrates, Chinese American home cooking--whether best with rice, made for noodles, perfect on the grill, or banquet-worthy for family and friends."--Back cover
t t t t t t Index.
Includes index.
Keywords: Cookbooks; Cooking, Chinese; Cookbooks